Desarrollo de una herramienta para planear el costo de las actividades asociadas a la perforación de un pozo de petróleo convencional vertical para las empresas del sector de hidrocarburos en Colombia (2014)
The objective of this project is the development of a standardized tool to plan the cost of the activities associated with the drilling of a vertical conventional oil well for companies in the hydrocarbon sector in Colombia. The development of this tool seeks to contribute to the competitiveness and productivity of companies in the hydrocarbon sector in Colombia, because the tool will allow costing oil wells with deviations of less than 10%, making the tool more accurate and accurate. Likewise, with the development of the same one will be able to realize changes of agile and efficient way without altering the formulation of obtaining of the budget. The tool will allow to plan, control and evaluate accurately and efficiently the cost of drilling an oil well, allowing to optimize and prioritize the resources of each of the projects, reducing the costs incurred in re-processes during the execution of the same.